2017
DOI: 10.1007/s00431-017-3044-3
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria from bronchoalveolar lavage fluid from children with suspected chronic lower respiratory tract infection: results from a multi-center, cross-sectional study in Spain

Abstract: This cross-sectional study assessed the prevalence of bacteria isolated from Spanish children with suspected chronic lower respiratory tract infection (LRTI) for whom bronchoalveolar lavage (BAL) was indicated. BAL fluid (BALF) was collected from 191 children (aged ≥ 6 months to < 6 years, with persistent or recurrent respiratory symptoms, non-responders to usual treatment) and cultured. Nasopharyngeal swabs (NPSs) were also obtained and cultured to assess concordance of BALF and NPS findings in the same patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 44 publications
(58 reference statements)
2
18
0
1
Order By: Relevance
“…These findings are consistent with previous studies in young children with chronic lower airway disorders including CF and bronchiectasis when using either oropharyngeal or nasopharyngeal swab data alone to predict lower airway infection . Although our data are unique, as we examined both oropharyngeal and nasopharyngeal bacterial cultures and compared them to BAL culture, we found that the combined approach added little to predicting lower airway bacterial infection.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These findings are consistent with previous studies in young children with chronic lower airway disorders including CF and bronchiectasis when using either oropharyngeal or nasopharyngeal swab data alone to predict lower airway infection . Although our data are unique, as we examined both oropharyngeal and nasopharyngeal bacterial cultures and compared them to BAL culture, we found that the combined approach added little to predicting lower airway bacterial infection.…”
Section: Discussionsupporting
confidence: 90%
“…Staphylococcus aureus , Pseudomonas aeruginosa , and Haemophilus influenzae were the major pathogens in children with CF, and they also predominated in oropharyngeal cultures . In contrast, Streptococcus pneumoniae , H. influenzae , and Moraxella catarrhalis were the main bacteria detected in nasopharyngeal and BAL specimens in children with bronchiectasis and other chronic lower airway infections . A common feature was the poor positive, but high negative predictive values of upper airway cultures for diagnosing lower airway infection.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Bronchoalveolar lavage fluid (BALF) cultures are a reliable method to determine the bacterial etiology of LRI [ 3 ]. Whether there is a difference between the culture results obtained from sputum samples and BALF is currently unclear.…”
Section: Introductionmentioning
confidence: 99%